In Situ Imaging of Dislocation Expansion in FZ‐Si Seeds During Temperature Ramp Heating Process. Issue 14 (21st May 2018) - Tsoutsouva, Maria G.; Riberi‐Béridot, Thècle; Regula, Gabrielle; Reinhart, Guillaume; Baruchel, José; Mangelinck‐Noël, Nathalie
Abstract : The impact of the thermal field in a directional solidification furnace on the generation and propagation of dislocations is investigated in intrinsic floating zone single crystal silicon. Seeds with different crystallographic orientations are wire‐cut from mono‐crystalline wafers and dislocation sources are solely left at the edges. Thermal annealing experiments are carried out in situ at the European Synchrotron Radiation Facility (ESRF) and the evolution of the silicon crystalline quality is studied by X‐ray diffraction imaging technique. At 1073 K, dislocations nucleate only at the edges and their strain field remains local. At higher temperature (1373 K), dislocations propagate throughout the entire width of the seed via the preferential activation of slip planes, related to the crystallographic orientation of the seed. These results confirm the high importance of seed preparation in mono‐like silicon growth process. Both mechanical and chemical polishing of all seed surfaces, including their edges, are mandatory to prevent dislocation expansion and multiplication. Abstract : Dislocation generation and propagation, in intrinsic floating zone silicon, is investigated in situ at the European Synchrotron Radiation Facility (ESRF). Thermal annealing experiments are carried out in a directional solidification furnace and the evolution of the silicon crystalline quality is studied by X‐ray diffraction imaging technique. Sources of dislocation are activated solely at the edges of the sample, due to a stress perpendicular to its main surface.